Concurrent superior semicircular canal dehiscence and endolymphatic hydrops: A novel case series. (January 2021) - Johanis, Michael; De Jong, Russell; Miao, Tyler; Hwang, Leslie; Lum, Meachelle; Kaur, Taranjit; Willis, Shelby; Arsenault, John J.; Duong, Courtney; Yang, Isaac; Gopen, Quinton
Highlights: SSCD and EH are two uncommon inner ear disorders. UCLA is a high-volume otologic referral center with the most SSCD cases worldwide. Three patients presented with both SSCD and EH, which have overlapping symptoms. Post-surgical persistence of shared symptoms may prompt an investigation for EH. Concurrent SSCD and EH is a rare but treatable entity. Abstract: Introduction: Superior semicircular canal dehiscence (SSCD) is characterized by CT-confirmed bony erosion over the superior semicircular canal, creating vestibular and auditory symptoms. Endolymphatic hydrops (EH) is characterized by an MRI-confirmed excess of endolymph within the scala media that distorts the membranous labyrinth. While there is overlap in symptoms, the two diseases result from different pathophysiologies and require different interventions. Presentation of cases: A retrospective chart review was conducted at the University of California, Los Angeles on a database of 270 adult SSCD patients, gathered between March 2011 and February 2020. A review of clinical notes, post-operative findings, and imaging was performed for 16 patients who had both CT-confirmed SSCD and an MRI of the internal auditory canal (IAC). Three cases of concurrent SSCD and EH were identified. Medical and surgical history, symptom progression pre- and post-operatively, and treatment outcomes were gathered. One patient's symptoms were resolved via mycophenolate mofetil, another's via hydrochlorothiazide, and the third's via hydrochlorothiazide and bilateral hearing aids. Discussion: Post-surgical persistence of SSCD symptoms that are mutually shared with EH is the strongest indicator that a physician should investigate for concurrent EH. VEMP and audiogram testing in these cases can be misleading and should not be relied on as rule-in or rule-out tests. Conclusion: Concurrent SSCD and EH is a rare but treatable entity. Physicians should consider ordering an MRI of the IAC if SSCD patients' symptoms persist or recur after a successful surgery.